The Influence of Organizational Culture, Leadership, and Motivation on Performance of Early Childhood School Teachers - Kiki Setyawati (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
The purpose of this research is to investigate the impact of organizational culture on teacher performance; the impact of the principal's leadership on teachers' performance; motivation's impact on teachers' performance; and how motivation, principal leadership, and organizational culture affect teachers' performance. The research used a quantitative method and a questionnaire as a research instrument. Data were collected from forty-five Early Childhood School Teachers. The gathered data is then examined utilizing a quantitative approach to simple linear regression analysis and multiple linear regression analysis. The analysis's findings indicate that, with a value of 0.618 > 0.05 and a t-count value of 0.502 < t-table 2.019, the organizational culture variable had no discernible impact on teachers' performance. With a value of 0.001 < 0.05 and a t-count of 3.751 > t-table of 2.019, the principle leadership variable has a positive and substantial impact on teacher performance. With a value of 0.033 < 0.05 and a t-count of 2.208 > t-table of 2.019, the motivating variable has a positive and significant impact. With a significance level of 0.000 < 0.05 and an f-count value of 30.968 > f-table 2.83, the factors organizational culture, principle leadership, and motivation have a significant and simultaneous impact on teacher performance